Analysis of Operating Conditions on Osmotic Dehydration of Plums (Prunus Domestica L.) and 3D-Numerical Determination of Effective Diffusion Coefficients - Rodriguez, Maria Marcela (2017)
The objective of this work was to analyze the relevant process conditions on osmotic dehydration of plums and to determine the diffusion coefficients related to this process. The influence of solution (type and concentration of solute, temperature, fruit/solution ratio) and process time on water loss, water content and solutes gain were studied. Process analysis was performed experimentally by means of a set of 16 duplicate tests and numerically by mathematical modeling of the unsteady-state mass transfer phenomena. Experiments were carried out with glucose and sorbitol solutions (40-60% w/w), dehydrating plum pieces during 2 h at temperatures of 25 and 40°C, with fruit/solution ratios of 1/4 and 1/10. For calculating effective diffusion coefficients, a novelty inverse-method was applied, the approximate shape of food-pieces was considered using Finite Elements Method. Calculated diffusion coefficients ranged from 1.13 × 10-09 to 4.71 × 10-09 m2 s-1 and 0.44 × 10-09 to 3.46 × 10-09 m2 s-1, for water and solutes, respectively.